DOI: 10.1016/s0742-3322(07)24017-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Implications of Valuation: Evidence from Valuing Growth Options

Abstract: Strategy is ultimately aimed at creating shareholder value, placing valuation in a central role linking finance and strategy. Focusing on growth options, this paper uses a unique -perfect information‖ model to examine, from a strategy point of view, the relationship between the market value of the firm and its intrinsic, or DCF, value. Although the research is at the level of the firm, the results have implications at the level of individual strategies and projects, since a firm can be conceptualized as a coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Kester (1984) estimates growth option value for a small sample of firms across five US industries, and he finds that many firms have a growth option value greater than 50%, but growth option values are unevenly distributed across firms and industries. Related work has adopted the same approach to calculating growth option value (e.g., Alessandri, Lander, & Bettis, 2007;Brealey & Myers, 2000;Long, Wald, & Zhang, 2005;Strebel, 1983).…”
Section: Defining Growth Option Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Kester (1984) estimates growth option value for a small sample of firms across five US industries, and he finds that many firms have a growth option value greater than 50%, but growth option values are unevenly distributed across firms and industries. Related work has adopted the same approach to calculating growth option value (e.g., Alessandri, Lander, & Bettis, 2007;Brealey & Myers, 2000;Long, Wald, & Zhang, 2005;Strebel, 1983).…”
Section: Defining Growth Option Valuementioning
confidence: 99%
“…Strebel (1983) examines the computer and data processing industry and finds that firms in this industry differ greatly in their growth option values. Kester (1984) documents the large heterogeneity of growth option value across industries, as well as across firms (also see Alessandri et al, 2007). Long et al (2005) also find evidence that a firm's growth option value is positively related to its R&D intensity and the level of industry concentration, which are proxies for firm and industry factors.…”
Section: Firm and Industry Effects On Growth Option Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Average real sales account for 186.9 billion yen (FY 2008) including very small companies like SPC ELECTRONICS CO. with only 12.8 billion yen of real sales and the top global players in the industry such as HITACHI with 11,193 billion yen in revenues. To construct a measure of expected real sales growth in electronics sector, due to the limited availability of growth forecasts for long time series I followed "perfect foresight" approach similar to Alessandri et al (2007) as if investors knew accurately next year sales growth. Sector efficiency was lowest in FY2002, when Japanese economy entered a recession phase and asset turnover of electronics companies accounted for mere 0.81× on average.…”
Section: Independent Variables: Firm-specific Factorsmentioning
confidence: 99%
“…He showed that the value of growth opportunities may account for a large and in some cases dominant portion of firms' market value (on average, 41.9% using 15% discount rate or 65.1% using 25% discount rate). Other researches (Alessandri et al 2007;Tong and Reuer 2006, etc. ) further tested the validity of Kester's model on larger samples of UK and US companies.…”
Section: Introductionmentioning
confidence: 96%